3-Trinitromethyl-4-nitro-5-nitramine-1H-pyrazole: a high energy density oxidizer. (15th August 2019) - Xiong, Hualin; Yang, Hongwei; Cheng, Guangbin
Abstract : A novel oxygen-rich compound was designed and synthesized. The combination of high density, positive heat of formation, high positive oxygen balance, high specific impulse and high detonation performance makes it a promising high energy density oxidizer. Abstract : A novel oxygen-rich energetic compound, 3-trinitromethyl-4-nitro-5-nitramine-1 H -pyrazole (5 ), was obtained by one-step nitration of 2-(3-amino-1 H -pyrazol-5-yl)acetic acid (4 ). Compound5 was characterized by IR and NMR spectroscopy, elemental analysis and differential scanning calorimetry (DSC). Additionally, the structure of compound5 was further confirmed by X-ray crystallography. Compound5 has a high density (1.90 g cm −3 ), positive heat of formation (0.99 kJ g −1 ) and positive oxygen balance (24.8%). The calculated detonation velocity ( D = 9124 m s −1 ) and pressure ( P = 37.2 GPa) are superior to those of RDX ( D = 8795 m s −1, P = 34.9 GPa). The calculated specific impulse of compound5 (262 s) is higher than that of AP (157 s) and ADN (202 s). The combination of these attractive properties makes it a promising high energy density oxidizer.